Peran Kebijakan Pendidikan dalam Meningkatkan Kualitas Pendidikan Bagi Peserta Didik - Tengku Darmansah; Anggi Anggraini; Fauzan Azhima Sirait; Nurkhotima Nurkhotima; Wardah Sahrani Sibarani (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
Education policy functions as a framework that sets educational standards and goals, so as to ensure that all students have equal access to resources and learning opportunities. Through the development of relevant curricula and quality teacher training, education policies can improve teacher competency, which in turn has a positive impact on student learning outcomes. In addition, educational policies also include systematic monitoring and evaluation to identify areas of improvement, thereby enabling the necessary adjustment strategies to meet students' needs more effectively. This research aims to determine the role of change management in order to determine the role of educational policy in improving the quality of education for students. In this research, qualitative methods were used through literature. Well-designed education policies can improve access to education for all students. Education policy also plays an important role in improving the quality of teaching through continuous training for teachers. Participation of parents and communities in supporting educational policies.